PENGARUH ACCELERATED LEARNING (PEMBELAJARAN CEPAT) TERHADAP KETERAMPILAN MENULIS PARAGRAF NARASI OLEH SISWA KELAS X SMA NEGERI 10 MEDAN TAHUN PEMBELAJARAN 2012/2013 - AYU WIRA ANGGRAINI (Universitas Negeri Medan, 2014)
This study aimed to investigate the effect of Accelerated Learning(Quick Learning) to paragraph narrative writing skills class X SMANegeri 10-year field study 2012/2013. The population of this studywere all students of class X SMA Negeri 10 field consists of 6classes with a student population of 242 people. Of the number ofstudents was drawn randomly sample 76 students. The method usedin this study is an experimental method to design research groupposttest only design (two groups) comparing two groups, theexperimental group were given learning to write narrativeparagraphs Accelerated Learning approach (Quick Learning) whilethe control group using Expository Teaching (Teaching indirectly)in learning to write narrative. The instrument used is a narrativeessay writing test. The average value of the experimental class was79.42 while the control class is 68.73. Thus it can be said that theaverage value of the test write narrative paragraphs in theexperimental class higher than the control class. Hypothesis testingis done by using the test